2015
DOI: 10.1186/s12913-015-1077-8
|View full text |Cite
|
Sign up to set email alerts
|

“Neither we are satisfied nor they”-users and provider’s perspective: a qualitative study of maternity care in secondary level public health facilities, Uttar Pradesh, India

Abstract: BackgroundQuality of care provided during childbirth is a critical determinant of preventing maternal mortality and morbidity. In the studies available, quality has been assessed either from the users’ perspective or the providers’. The current study tries to bring both perspectives together to identify common key focus areas for quality improvement.This study aims to assess the users’ (recently delivered women) and care providers’ perceptions of care to understand the common challenges affecting provision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 33 publications
7
105
2
Order By: Relevance
“…Space constrained labour-rooms and obstructions caused by the use of curtain in attending to multiple women simultaneously have been cited as potential reasons that providers do not use curtains for privacy [11,5254]. Facility cleanliness in terms of clean linen in the wards, with frequent cleaning of the wards and toilets was a significant determinant of women’s overall satisfaction of services, which often are irregular and disorganised [5559].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Space constrained labour-rooms and obstructions caused by the use of curtain in attending to multiple women simultaneously have been cited as potential reasons that providers do not use curtains for privacy [11,5254]. Facility cleanliness in terms of clean linen in the wards, with frequent cleaning of the wards and toilets was a significant determinant of women’s overall satisfaction of services, which often are irregular and disorganised [5559].…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions surrounding the quality of care that will be received in a facility impact a woman’s initial decision to deliver in a facility, in addition to whether she will access institutional delivery for subsequent births [6,7,10]. Although women in LMICs have reported that high-quality interpersonal interactions are directly related to satisfaction with care, research suggests that providers may consider elements such as respect, privacy, dignity and information-sharing to be less critical components of care that require immediate attention [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The supply of health services was also a commonly studied outcome and the majority of the included reliability articles focused on the effects of electricity interruptions on health service delivery or healthcare quality, with most finding a negative association. In a qualitative study assessing users' and providers' perceptions of maternity care in India, for instance, Bhattacharyya, Issac, Rajbangshi, Srivastava, and Avan (2015) identified poor electricity reliability as a common challenge to delivering high quality care in Indian health facilities (Bhattacharyya et al, 2015). Indeed both health care users and providers noted the importance of a regular supply of electricity, with one provider remarking that a lack of fuel funding constrained the use of the generators, such that deliveries sometimes had to be conducted by candle light (Bhattacharyya et al, 2015).…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 99%
“…Working women tend to have lower satisfaction levels with childbirth services compared with homemakers [16]. Having a fear of childbirth and/or postnatal depressive symptoms has a negative and compounding association with satisfaction [1719]. …”
Section: Introductionmentioning
confidence: 99%
“…Labour rooms have become crowded and understaffed and face shortages of equipment and material [17,40] and the documentation processes around childbirth have been described to be ‘too much to do concurrently with actual care provision’, with care providers relying on verbal communication rather than maintaining written documentation of decision-making around childbirth [17,41]. Qualitative studies exploring Indian women’s experiences and opinions on giving birth at a health facility reveal that they are not fully satisfied with their childbirths, primarily due to the long waiting time before they meet a healthcare provider, having few opportunities to communicate with providers, not being involved in decision-making, and having stern care providers [17,35,42,43]; however, they settle for childbirth services perceived as ‘essential’ for safe childbirth rather than ‘desirable’ for a pleasant experience [17,44,45]. …”
Section: Introductionmentioning
confidence: 99%